The Relationship Between Preferred Learning Styles and Academic Achievement of Undergraduate Health Sciences Students Compared to Other Disciplines at a Middle Eastern University Utilizing the VARK Instrument - Gangadharan S; Al Mezeini K; Gnanamuthu SS; Al Marshoudi KA (Advances in Medical Education and Practice)
Shobana Gangadharan, Khamis Al Mezeini, Sumathi Sasikala Gnanamuthu, Khadija A Al Marshoudi College of Health Sciences, University of Buraimi, Buraimi Governorate, OmanCorrespondence: Shobana Gangadharan, College of Health Sciences, University of Buraimi, P.O Box 890, Al Buraimi, Postal Code 512, Oman, Tel +968 92474074, Email shobana@uob.edu.omIntroduction: Learning style denotes a learner’s approach to acquiring, processing, interpreting, organizing, and contemplating information. VARK, formulated by Fleming and Mills (1992), assesses learning styles: Visual (V), Aural (A), Reading/Writing (R), and Kinesthetic (K). Visual learners prefer observing; Aural learners favor listening to lectures; Reading/Writing learners engage through texts and notes; Kinesthetic learners benefit from tactile activities.Purpose: To compare learning style preferences of undergraduate health sciences students with other disciplines and examine the relationship between VARK scores and academic performance.Methods: A cross-sectional study of 347 undergraduate students recorded demographic data and responses to the Arabic version of the VARK questionnaire. Data were analyzed using SPSS version 27 which included descriptive and inferential statistics.Results: Unimodal preferences were most common, ranging from 47.4% to 51.4% in the College of Health Sciences and 11.8% to 15.0% in the College of Law as the least. Quadmodal preferences were rare but more frequent in Health Sciences and Engineering. Auditory (A) was the most preferred unimodal style (Mean/SD - 3.72/2.181), while kinesthetic (Mean/SD - 0.54/.864) was the least preferred. Mann–Whitney U-test results indicated Health Sciences students scored higher in K (Z = − 4.558, p< 0.001) and total VARK scores (Z = − 3.633, p< 0.001). There was a statistically significant difference in CGPA between unimodal and multimodal learners (Z = − 2.150, p=0.032), with unimodal learners ranking lower.Conclusion: The findings suggest that multimodal learners outperformed unimodal learners, even though unimodal learners constituted a larger group. The Health Sciences and Engineering students exhibited marginally higher Quadmodal learning preferences than other disciplines, indicating the need for comprehensive and engaging learning experiences. These results have practical implications for educators, who should consider learning styles to enhance teaching strategies, address unique student challenges, and create an inclusive educational environment.Keywords: learning style, VARK, academic achievement, health sciences, university, undergraduate students